Notes relating to the flora of Bhutan: XXXIX. Gramineae II - Noltie, H. J. (Edinburgh Journal of Botany, 1999)
The following descriptions of new taxa, new combinations, lectotypifications, and nomenclatural notes are required for the forthcoming volume of the Flora of Bhutan (volume 3, part 2, Gramineae). New species: Agrostis ushae Noltie from India (Sikkim), Arundinella dagana Noltie and Cymbopogon bhutanicus Noltie from Bhutan. New subspecies: Deschampsia cespitosa subsp. sikkimensis Noltie from India (Sikkim) and China (Tibet). New combinations: Agrostis petelotii (Hitchc.) Noltie, Urochloa supervacua (C.B. Clarke) Noltie, Cymbopogon munroi (C.B. Clarke) Noltie, Urochloa villosa var. barbata (Bor) Noltie, Themeda triandra var. laxa (Andersson) Noltie. The following species are reported here for the first time from the following countries. Bhutan: Neyraudia curvipes Ohwi, Tripogon purpurascens Duthie, Elymus duthiei (Melderis) G. Singh, Urochloa panicoides P. Beauv., Spodiopogon lacei Hole, Microstegium falconeri (Hook.f.) Clayton. China (Yunnan): Agrostis zenkeri Trin. Bangladesh: Panicum laxum Sw.
Keywords: Bangladesh; Bhutan; China; Gramineae; India; lectotypifications; new combinations; new records; new taxa; Sikkim; Tibet